Effect of fluid intake on performance, body temperature, and body weight loss during swimming training - Taimura, A.; Sugahara, M. (Medicine & Science in Sports & Exercise, 1996)
Nine male swimmers performed 20 x 50 m repetitions on one minute interval. On every fourth interval, 50 ml of water was consumed. It was found that fluid intake contributed to sustained performance and suppressed body temperature. Although swimmers performed in a "wet" environment, fluid intake was necessary to prevent dehydration. Implication. Swimmers should drink frequently during swimming practices. The frequency is possibly more than one might expect.